Claiming Notability for Women Activists in Religion - Hartung, Colleen (Women in Religion, 2020)
This volume includes 10 biographies about the life and work of women activists, noteworthy in their particular religious or spiritual contexts yet not identified as notable, or at least not notable enough to have a biographical article on Wikipedia. It also includes a theoretical chapter rethinking the concept of notability in relation to the quality and character of what is covered in these biographies. Each biographical chapter makes the case for its subject's notability. The work of these women as founders and leaders in the "great man" tradition is amplified and made visible, but their work as coalition builders, collaborators, mentors, facilitators of resistance movements and more, is also held up as an essential part of their notable character. Collectively, the chapters in this volume work to leverage the concept of notability in ways that challenge and extend our understanding of this concept. This work provides useful, critical engagement with the concept of notability as an important aspect of biographical writing in general and of Wikipedia standards in particular for people who write biographies about women and the librarians who help them. This engagement is needed if we are to move the dial on gender bias around the biographical coverage of women generally and on Wikipedia in particular.